ZeroHarm Mobile App - Alvarez, Vincent (Wellington Faculty of Engineering Symposium, 2023)
Maintaining the health and safety of workers on a worksite should be a site’s number one priority. For a worksite to uphold a high level of safety it must keep track of things like possible hazards, substances, incidents, and workers coming in and out of a site. Keeping track of all this data and keeping workers aware of this information and any updates that occur is not easy to do in real time. With the ZeroHarm mobile app, workers can sign in and out of sites while also having and receiving updates on information like hazards and locations on the site which may be harmful. This app is built in React Native and makes use of the internet to communicate information. This project has produced a working prototype app to this idea. This app was evaluated through both unit testing within the React Native environment and user tested by real site-workers.